Building an Inclusive Community for Agama and Kepercayaan Groups: a Case Study of Indonesia Merayakan Perbedaan (IMP) of East Java - Asep Sandi Ruswanda; Samsul Maarif (Religio: Jurnal Studi Agama-agama, 2021)
This study focuses on Indonesia Merayakan Perbedaan (IMP)’s works to build social inclusion for agama (religion) and kepercayaan (faith) groups. The Constitutional Court’s decision No. 97/PUU-XIV/2016 was for sure a political turning point expected to eliminate stigma, discrimination, and recognition gaps between agama and kepercayaan groups. However, those were still prevalent. More alternative and creative work is still in need. This study demonstrates that IMP can be a model for building an inclusive community for agama and kepercayaan groups. IMP found ways to effectively instrumentalize the decision for diversity celebration. It managed diversity for inclusion in four phases: 1) raising awareness, creating understanding and encouraging reflection, 2) developing a vision of inclusion, 3) rethinking key management concepts and principles, and 4) adapting systems and processes. In doing so, IMP maximized opportunities and minimized challenges for the sustainability of its work in building an inclusive community. IMP’s participation in building social inclusion was a form of community intervention at a community level on ecological pathways to social inclusion. This study argues that community intervention such as IMP is significantly considerable to promote individual, organizational, community, and socio-political transformations to social inclusion, especially for inclusive interreligious relationships for agama and kepercayaan groups.